El payador - Lugones, Leopoldo, 1874-1938 (Historia (Linkgua), 2013)
Leopoldo Lugones Argüello's first book of poems, Las montañas del oro, contained measured and free verse prose and appeared during the height of modernism. Later he published two more collections inspired by Rubén Darío. Odas seculares marked a change in his style, exalting the Argentine riches inspired by Virgil. His poetry becomes intimate in later works, and some of his posthumous poems have a more narrative style.